Evaluation of the Relationship Between Nomophobia and Anxiety Level in Young People: An Example From Turkey - KIVANÇ, MERAL MADENOĞLU; Yılmaz, Ülkü; ÇETİN, AYKE NİSA; SABA, EMRE ESER (Taylor & Francis Ltd., 2025)
With the development of communication technology, smartphones have started to fulfill many functions. Frequently used smartphones can cause health problems. Nomophobia is one of these disorders and is known as the fear of being away from cell phones. In this study, it was aimed to examine the relationship between nomophobia and anxiety levels of health sciences faculty students.The study was conducted with 383 students (in the departments of nursing, nutrition and dietetics, physiotherapy and rehabilitation) in the faculty of health sciences of a foundation university between November 2022 and June 2023. The study data were collected by face-to-face questionnaire method. 'Descriptive Data Form', 'Uskudar Nomophobia Scale' and 'Anxiety Rating Scale' were used to collect data. SPSS 24 statistical program was used in the analysis of the study. When the smartphone usage characteristics of the participants were evaluated, it was found that 42.6% of them were anxious when the battery ran out, 44.1% of them sometimes thought that the smartphone affected their academic success, 39.9% of them sometimes delayed eating and sleeping, 50.9% of them thought that the smartphone had physical, psychological and social harms, 46% of them sometimes thought that they were dependent on the smartphone. As the level of nomophobia increases, the anxiety level and sub-dimension scores of individuals increase. When the relationship between nomophobia level and anxiety level was evaluated; it was determined that the level of impairment in functionality, overuse, inability to communicate, and anxiety level of individuals increased as the level of nomophobia increased.
Keywords: Addiction; Anxiety; Nomophobia; Smartphone; Smartphone Addiction